2017
DOI: 10.1038/s41598-017-10751-x
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing no-photon exciton generation chemistry to engineer semiconductor nanostructures

Abstract: Production of semiconductor nanostructures with high yield and tight control of shape and size distribution is an immediate quest in diverse areas of science and technology. Electroless wet chemical etching or stain etching can produce semiconductor nanoparticles with high yield but is limited to a few materials because of the lack of understanding the physical-chemical processes behind. Here we report a no-photon exciton generation chemistry (NPEGEC) process, playing a key role in stain etching of semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…This result confirms the efficiency of the acid treatment and provides further support for the NPEGEC. Previously our research group managed to stain etch cubic SiC and used that porous material to fabricate nanoparticles using reactants that were selective for 3C-SiC [26]. In order to compare the 3C and the 6H polytypes, two samples were etched by their dedicated reactants and were investigated by SEM/FIB.…”
Section: Chemical Etching and Morphology Of The Bulk 6h-sicmentioning
confidence: 99%
See 1 more Smart Citation
“…This result confirms the efficiency of the acid treatment and provides further support for the NPEGEC. Previously our research group managed to stain etch cubic SiC and used that porous material to fabricate nanoparticles using reactants that were selective for 3C-SiC [26]. In order to compare the 3C and the 6H polytypes, two samples were etched by their dedicated reactants and were investigated by SEM/FIB.…”
Section: Chemical Etching and Morphology Of The Bulk 6h-sicmentioning
confidence: 99%
“…Thus, there is an urgent need for finding a method which allows the preparation of porous SiC by electroless etching. In our previous study [26], we proposed a new method that could give us better insight and understanding of physico-chemical processes behind the stain etching of semiconductors, which is a common method to obtain nanostructures. The "no photon exciton generation chemistry" (NPEGEC) suggests that the position of the band edge with respect to the potential of the reactants is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SiC QDs can be used as stable light sources for sensors, cell imaging, and light‐emitting diodes . On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers . For the SiC QDs with very small sizes, their surface defects play important roles in luminescence .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers . For the SiC QDs with very small sizes, their surface defects play important roles in luminescence . The study had indicated that for the SiC QDs smaller than 1 nm, the surface defect‐related luminescence dominates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation